Twins! - Scott, Elaine, 1940-; Miller, Margaret, 1945- (New York : Atheneum Books for Young Readers, 1998)
Photographs and text teach young readers about twins, looking at some things that are the same, and things that are different about twins, and presenting the message that everyone is unique and special.
School Library Journal
Booklist
Kirkus Review
3.5
K-3
Keywords: Twins -- Juvenile literature; Twins; Twins